Architectural Design of an Executive Information System (EIS) to Support Strategic Decision-Making in the Government Sector - Setiadi, Farisya; Rubhasy, Albaar; Muhaemin (Cattleya Darmaya Fortuna, 2025)
Indonesia is a country with great potential to play a significant role in globalization. Indonesia's potential lies in its highly strategic territory, cultural and biological diversity, and abundant human resources. However, this enormous potential requires sound management to achieve prosperity for the Indonesian people. The government is the most important component in the state administration that runs the wheels of government. However, to date, the government is considered slow and ineffective in making strategic decisions. To make strategic decisions, tools are needed to assist leaders in carrying out their duties. This paper presents an EIS architectural design containing techniques and technologies divided into layers: collection, processing, analysis, presentation, and management. These layers are mutually supportive and integrated, serving as a guideline for the development of an Executive Information System (EIS) that functions to support strategic decision-making within the government sector.